2011
DOI: 10.1158/0008-5472.can-11-1154
|View full text |Cite
|
Sign up to set email alerts
|

Metabolomic Profiling Reveals Potential Markers and Bioprocesses Altered in Bladder Cancer Progression

Abstract: While alterations in xenobiotic metabolism are considered causal in the development of bladder cancer (BCa), the precise mechanisms involved are poorly understood. In this study, we used high-throughput mass spectrometry to measure over 2,000 compounds in 58 clinical specimens, identifying 35 metabolites which exhibited significant changes in BCa. This metabolic signature distinguished both normal and benign bladder from BCa. Exploratory analyses of this metabolomic signature in urine showed promise in disting… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
168
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
3

Relationship

3
7

Authors

Journals

citations
Cited by 174 publications
(181 citation statements)
references
References 27 publications
12
168
0
1
Order By: Relevance
“…Metabolomics methods could be used to monitor changes of specific metabolism in process of tumor development, to predict tumor progression, to monitor tumor response to intervention, to determining a characteristic metabolic pattern for cancer patients, to identify tumor associated biomarkers and to provide helps for early diagnosis, prognosis evaluation and efficacy analysis for cancer patients. Metabolomics has been successfully applied to biomarkers screening for many cancers, such as bladder [10], colon [11], lung [12] and prostate cancers [13]. However, metabolomics studies on breast cancer is rarely reported.…”
Section: Introductionmentioning
confidence: 99%
“…Metabolomics methods could be used to monitor changes of specific metabolism in process of tumor development, to predict tumor progression, to monitor tumor response to intervention, to determining a characteristic metabolic pattern for cancer patients, to identify tumor associated biomarkers and to provide helps for early diagnosis, prognosis evaluation and efficacy analysis for cancer patients. Metabolomics has been successfully applied to biomarkers screening for many cancers, such as bladder [10], colon [11], lung [12] and prostate cancers [13]. However, metabolomics studies on breast cancer is rarely reported.…”
Section: Introductionmentioning
confidence: 99%
“…These results suggest that β-oxidation may play an important role in BC tumorigenesis and possibly aggressiveness. Another study conducted by Putluri et al [20] also revealed that patients with BC have higher level of carnitine (Table 1).…”
Section: Carnitine Derivatives and Bladder Cancermentioning
confidence: 80%
“…Although urine may be directly related to genitourinary malignancies, the study also indicated that the metabolic profiles in the serum may reflect tissue metabolites. In addition, there have been metabolomic studies on bladder cancer [89][90][91][92].…”
Section: Genitourinary Cancermentioning
confidence: 99%